Interleukins The Immune and Non-Immune Systems' Related Cytokines - Behzadi, Payam (IntechOpen, 2021)
The immune system recruits a wide range of molecule groups and categories, each of which has its own function, property, and structure. Among these, interleukins play a pivotal role in supporting the immune and non-immune systems of the human body. Interleukins as effective cytokines participate in different conditions such as homeostasis, infectious diseases, autoimmune diseases, and cancers. This unique property of interleukins makes them invaluable biomarkers that can be used as important biosensors. This book is divided into three sections: "Interleukins' Classification and Evolutionary Features", "Autoimmune Diseases and Low Immune System", and "Cancer and Injuries". Chapters examine the role of various interleukins in conditions such as leukemia, rheumatoid arthritis, and allergic and autoimmune diseases.